Private security and national security: The case of Estonia. (November 2022) - Light, Matthew; Singh, Anne-Marie; Gold, Josh
Most studies of private security postulate exclusively internal, primarily economic, causes of the industry's growth and regulation. In contrast, based on the case of post-Soviet Estonia, we investigate how a state's external security environment influences private security. Estonia's tense relations with neighbouring Russia and related pursuit of EU and NATO membership have generated several policies through which private security evolved from a lawless, politically contested industry to a modest, lightly regulated one: (1) the exclusion of public police from private security and an effective campaign against organized crime that together enabled an autonomous and non-criminalized security industry to emerge, (2) free-trade policies that permitted western companies to acquire Estonian security firms, and (3) an 'all-of-nation' approach to national security that promotes comprehensive state-civil society security cooperation. Estonia thus clarifies how high politics shapes private security, while also revealing the factors that make the industry relatively uncontentious in most industrialized democracies.